إشكاليات تحديد معاني الكلمات المترادفات في عملية الترجمة - Fikri, Shofil (UIN Maulana Malik Ibrahim Malang, 2020)
Synonyms include cultural loads that stand in the background and surround the original text, and that culture and language have a close relationship, as culture is the body and language is its heart. However, when performing the translation process, the translator may be forced to fill some linguistic, stylistic or cultural gaps, in order to best communicate the content of the translated text to the recipient. This article aims to identify the difficulties that the translator faces in choosing the exact term during the translation process. This article uses a descriptive method for presenting data related to the topic. As for the data sources used, they were taken from some appropriate academic books and journals and are in line with this article. The results that I have communicated to indicate that the translation process is a more complex and difficult matter, and in this case the translator does not find the time at all, to refer to the dictionaries to know the exact opposite of the term he faces, but rather he must rely on his intuition and his mastery of the two languages to find an equivalent that helps the listeners to understand the translated speech.